Active standby village/sub-district transformation after the COVID-19 pandemic - Novianti, Diana (BKM Public Health and Community Medicine, 2021)
Objective: The standby village is part of the community empowerment effort developed since 2006 to accelerate the achievement of the Millennium Development Goals. The standby village activities mainly provide primary health services and community empowerment through developing community-based health efforts (UKBM). It encourages community-based surveillance, environmental health, health emergencies, disaster management, and clean and healthy living behavior (PHBS). The COVID-19 pandemic has given rise to various community-based activities made by the government and local initiatives at the village level. Not all villages/subdistricts are responsive and independent in efforts to control and prevent diseases, including COVID-19, by the elements in active-standby villages/subdistricts. Active-standby villages/subdistricts have the potential to play a role in controlling and preventing COVID-19 and being developed for handling other health problems. Content: Strengthening the health system starting from the countryside has a big impact because rural areas are vulnerable to public health crises. In dealing with post-pandemic conditions, it is necessary to transform the health system by utilizing its potential in disease-tracking activities from the central to the village level, an increase in the budget for health financing, an increase and distribution of health workers in all regions, and an adjustment of health services based on the values ​​prevailing in the local community. More than 83 thousand villages/subdistricts with high enough social capital make the health system at the rural level have the potential to help solve health problems, including COVID-19. Strengthening the active-standby village/subdistrict program and increasing development efforts through the role of the village government needs support from the district/city government, as well as integration with community empowerment programs to have a broader impact on the community. The strengthening and development of active-standby villages/subdistricts will bring a healthy, caring, and responsive community to health problems in their area. Objective: Desa siaga adalah bagian dari upaya pemberdayaan masyarakat yang dikembangkan sejak tahun 2006 sebagai bentuk percepatan pencapaian Millennium Development Goals. Kegiatan desa siaga terutama adalah penyediaan pelayanan kesehatan dasar, pemberdayaan masyarakat melalui pengembangan UKBM, mendorong upaya survailans berbasis masyarakat, kedaruratan kesehatan dan penanggulangan bencana serta penyehatan lingkungan, dan PHBS. Pandemi COVID-19 telah memunculkan berbagai kegiatan berbasis masyarakat baik itu yang dibuat pemerintah maupun inisiatif lokal di tingkat desa. Belum semua desa/kelurahan tanggap dan mandiri dalam upaya pengendalian dan pencegahan penyakit termasuk COVID-19 sesuai dengan unsur yang ada pada desa/kelurahan siaga aktif. Desa/kelurahan siaga aktif berpotensi untuk dapat berperan dalam pengendalian dan pencegahan COVID-19 dan dikembangkan untuk penanganan masalah kesehatan lainnya. Content: Penguatan sistem kesehatan mulai dari pedesaan memberikan dampak yang besar karena wilayah pedesaan cukup rentan terhadap krisis kesehatan masyarakat. Dalam menghadapi kondisi pasca pandemi diperlukan transformasi sistem kesehatan dengan memanfaatkan potensi dalam kegiatan pelacakan penyakit. Diperlukan kebijakan yang sama dari tingkat pusat hingga desa, penambahan anggaran pembiayaan kesehatan, peningkatan dan pemerataan tenaga kesehatan di semua wilayah, serta penyesuaian layanan kesehatan yang berdasar pada nilai yang berlaku di masyarakat setempat. Lebih dari 83 ribu desa/kelurahan dengan modal sosial yang cukup tinggi membuat sistem kesehatan di tingkat pedesaan memiliki potensi dalam membantu penyelesaian masalah kesehatan termasuk COVID-19. Penguatan program desa/kelurahan siaga aktif serta peningkatan upaya pengembangan melalui peranan pemerintah desa perlu mendapat dukungan dari pemerintah kabupaten/kota, serta integrasi dengan program pemberdayaan masyarakat untuk memberikan dampak yang lebih luas kepada masyarakat. Penguatan dan pengembangan desa/kelurahan siaga aktif akan menghadirkan masyarakat yang sehat, peduli, dan tanggap terhadap masalah kesehatan di wilayahnya.